2010
DOI: 10.1364/oe.18.013708
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering microscope with shot noise limited sensitivity using subharmonically synchronized laser pulses

Abstract: We propose and demonstrate the use of subharmonically synchronized laser pulses for low-noise lock-in detection in stimulated Raman scattering (SRS) microscopy. In the experiment, Yb-fiber laser pulses at a repetition rate of 38 MHz are successfully synchronized to Ti:sapphire laser pulses at a repetition rate of 76 MHz with a jitter of <8 fs by a two-photon detector and an intra-cavity electro-optic modulator. By using these pulses, high-frequency lock-in detection of SRS signal is accomplished without high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 30 publications
0
75
0
Order By: Relevance
“…In general, CARS or Raman images at CH2 bend and stretch vibrational modes were widely used to detect lipid droplets inside the adipocytes. [34][35][36] In the case of fibroblasts, however, formation of lipid droplets depends on various conditions such as the composition of culture medium. In the present study, no droplet-like structure was observed in Fig.…”
Section: Imaging Of Mammalian Cellsmentioning
confidence: 99%
“…In general, CARS or Raman images at CH2 bend and stretch vibrational modes were widely used to detect lipid droplets inside the adipocytes. [34][35][36] In the case of fibroblasts, however, formation of lipid droplets depends on various conditions such as the composition of culture medium. In the present study, no droplet-like structure was observed in Fig.…”
Section: Imaging Of Mammalian Cellsmentioning
confidence: 99%
“…To implement high-sensitivity imaging in pump-probe microscopy, it is necessary to circumvent the intensity noise of the probe beam. In stimulated emission and stimulated Raman microscopy, the intensity of the pump beam is modulated at high frequency (>1 MHz) because the laser intensity noise of a solid state laser used for probing occurs primarily at low frequencies (from kilohertz to DC) in the form of 1/f noise [14,23,24]. However, in PT microscopy, the high-frequency modulation scheme reduces signal intensity because the time response of the PT signal is, in principle, determined by heat conductivity and is decreased by half at~1 MHz for a tightly focused laser beam [25][26][27][28].…”
Section: Improvement In Snr By the Spatially Segmented Balanced Detecmentioning
confidence: 99%
“…Although laser shot noise limit can be reached by MHz modulation in SRS microscopy [8][9][10]16], the signal to noise ratio (SNR) at low laser power is actually limited by the electronic noise of the LIA's input preamplifier. For an ideal voltage preamplifier the source of the electronic noise is the thermal Johnson-Nyquist noise of the input impedance,…”
Section: Introductionmentioning
confidence: 99%